Physical and optical waveguiding properties of solgel deposited nanostructured TiO2 thin films: a study on the effect of synthesis parameters. (2015) - Atoui, Mohamed; Touam, Tahar; Hadjoub, Ilhem; Chelouche, Azeddine; Boudine, Boubekeur; Fischer, Alexis; Boudrioua, Azzedine; Doghmane, Abdellaziz
In this paper, amorphous and polycrystalline nanostructured TiO2 thin films were prepared by solgel dipcoating process. The effects of different fabrication parameters (e.g., withdrawal speed, annealing temperature) on the structural, morphological and optical properties of the synthesised films were investigated by Xray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM) and UVvisible Spectrophotometry. Waveguiding properties such as propagating modes and optical loss were measured at 632.8 nm by Mlines spectroscopy (MLS). The results indicate that all thin films annealed at 500ºC exhibit XRD patterns and FTIR data consistent with the TiO2 anatase phase. AFM images have revealed that morphology and surface roughness of deposited thin films depend on withdrawal speed and heat treatment temperature. The UVvisible transmittance results show that all thin films were transparent with an average transmittance higher than 70% in the visible region. The results have also demonstrated from MLS measurements that TiO2 thin film slab waveguides deposited at withdrawal speed of 2 cm/min and annealed at 500°C exhibit not only better light confinement but also lower optical loss than those dipcoated at the speed of 1 and 3 cm/min.